2011
DOI: 10.1017/s0007114511004697
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover study investigating the effects of galacto-oligosaccharides on the faecal microbiota in men and women over 50 years of age

Abstract: Faecal microbial changes associated with ageing include reduced bifidobacteria numbers. These changes coincide with an increased risk of disease development. Prebiotics have been observed to increase bifidobacteria numbers within humans. The present study aimed to determine if prebiotic galacto-oligosaccharides (GOS) could benefit a population of men and women of 50 years and above, through modulation of faecal microbiota, fermentation characteristics and faecal water genotoxicity. A total of thirty-seven volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 60 publications
9
97
0
5
Order By: Relevance
“…24 There is also a report on GOS supplementation and its effect on bifido numbers in vivo and in vitro in women and men over 50 y old. 26 In conclusion: prebiotic oligosaccharides stimulate the development of bifidobacteria.…”
Section: Prebiotics Gut Metabolic Activity and Bifidogenic Effectmentioning
confidence: 98%
“…24 There is also a report on GOS supplementation and its effect on bifido numbers in vivo and in vitro in women and men over 50 y old. 26 In conclusion: prebiotic oligosaccharides stimulate the development of bifidobacteria.…”
Section: Prebiotics Gut Metabolic Activity and Bifidogenic Effectmentioning
confidence: 98%
“…C. difficile, Enterococcus faecium, Clostridium perfringens or Campylobacter) and enterobacteria. Regarding the prebiotic approach, the use of galacto-oligossaccharides has been successful in correcting microbiota changes and for improving the immunological state associated with the elderly 106,107 (Table 2), however intervention studies with alternative prebiotics (pectin, xilo-oligosaccharides, malto-oligosaccharides, etc) are lacking. Synbiotics have been also recently tested to improve age-related changes in the gut microbiota, with some positive effects on specific intestinal microbial populations ( Table 2).…”
Section: Nutritional Strategies For Restoring a Balanced Composition mentioning
confidence: 99%
“…Changes in some selected bacterial groups have been observed due to controlled changes to the normal diet e.g. high-protein diet (118,119) , prebiotics (97,(120)(121)(122) , probiotics (123)(124)(125) , weight-loss diet (20,126,127) and berries (128) . More specifically, changes in the type and quantity of non-digestible carbohydrates in the human diet influence both the metabolic products formed in the lower regions of the GI tract and levels of bacterial populations detected in faeces (129) .…”
Section: Dietary Interventions V Habitual Dietmentioning
confidence: 99%
“…The best sources of naturally occurring prebiotics may be found in vegetables such as artichokes, onions, chicory, garlic and leeks (167) . There are numerous studies in which the bifidogenic properties of prebiotics are shown (121,122,166,(168)(169)(170)(171) . In addition, increase in abundance of lactobacilli (121,122) and F. prausnitzii (170,172) has been shown.…”
Section: Prebioticsmentioning
confidence: 99%
See 1 more Smart Citation